Exploring the Implementation and Success of Nutrition Education Programs in Early Childhood Education Settings - Churiyah, Churiyah; Hasibuan, Rachma (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to explore the implementation and success of nutrition education programs in a kindergarten. The research utilized a qualitative approach through structured interviews with teachers and parents. Data were analyzed using data reduction techniques to identify key patterns and themes. The findings revealed that the nutrition program successfully improved childrenÔÇÖs eating habits, such as increased preference for healthy foods and reduced consumption of unhealthy snacks. Teachers employed interactive methods like storytelling and games, while parents supported the program by providing healthy meals at home. Challenges included children's preference for unhealthy snacks and parents' limited time. The study recommends developing more comprehensive programs, including parent training and the provision of engaging educational materials.┬á┬á┬á